2019
DOI: 10.2478/revecp-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Use of TOPSIS Method for Assessing of Good Governance in European Union Countries

Abstract: Good Governance presents the contemporary trend of managing public affairs worldwide. This concept is promoting the basic elements of subsidiarity, participation, and democracy in modern public administration. Presented article is focused on the evaluation of Good Governance development in the European Union countries in the long-term, in the period 2007–2017. The evaluation is based on the application of multiple criteria decision-making methods, concrete The Technique for Order Preference by Similarity to Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
1
7
0
2
Order By: Relevance
“…The main results emphasize that there are direct joint implications of each public administration dimension on economic development, research and development support, and socio-economic credentials, especially upon poverty reduction. Our results are consistent with several other studies from the literature [13][14][15]37,38].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The main results emphasize that there are direct joint implications of each public administration dimension on economic development, research and development support, and socio-economic credentials, especially upon poverty reduction. Our results are consistent with several other studies from the literature [13][14][15]37,38].…”
Section: Discussionsupporting
confidence: 94%
“…Merloni [36] (p. 107), cross-examining the public administration in European countries with similar dimensions as regards the size of the population and level of economic development, with a specific focus on Italy, concluded that "the basic factor driving this complexity is the country's size of population relative to its level of social and economic development". At the same time, Ardielli [37] appraised the good governance of the EU countries and pointed out countries that were flourishing in the long term, especially the Nordic states-Finland, Sweden, and Denmark, as well as countries with higher deficiencies in terms of good governance, such as Romania, Bulgaria, or Greece.…”
Section: Public Governance and Sustainable Developmentmentioning
confidence: 99%
“…Afterward, the matrix for each variant can be compiled, and also the partial utility function can be calculated. The partial utility of the y ij criterion is specified by Equation 10 [2,51].…”
Section: Application Of the Wsa Methods To Define The Final Variant Ramentioning
confidence: 99%
“…TOPSIS method is frequently used nowadays to solve problems in both public and private sectors, for example Karadayi and Karsak (2014) used TOPSIS for evaluation of performance in health system or Vrabková et al (2019) for evaluation of social care in the public sector of the Czech Republic. Ardielli (2019) used TOPSIS for the evaluation of good governance in public administration. The process of TOPSIS procedure is as follow:…”
Section: Model and Methodsmentioning
confidence: 99%